Daniel Moyano — el migrante de un incendio permanente y su condición del desarraigo-identidad entre la ciudad y las periferias, Buenos Aires y Madrid como un componente constitutivo de su literatura - Mehlbauer, Weronika (Romanica Silesiana)
Throughout his life Moyano’s traveled between Buenos Aires, Córdoba, La Rioja, and Madrid, which had an unquestionable influence on the author’s oeuvre. His work is often divided into two periods: one before the great emigration to Madrid (when he focused on the differences between the capital and the rest of the country, concentrating on the poverty and misery of the margins), and one which introduces a profound reflection on a man forced to live in exile, where the two worlds he knows, the present and the past, blend together leaving him deeply confused. Moyano was a peripheral author, always on the margin, far from the capital and far from his country. Key words: Daniel Moyano, exile, emigration, centre, periphery.